A Review of Scalable Hexagonal Boron Nitride (h‐BN) Synthesis for Present and Future Applications. Issue 6 (16th December 2022) - Naclerio, Andrew E.; Kidambi, Piran R.
Abstract: Hexagonal boron nitride ( h ‐BN) is a layered inorganic synthetic crystal exhibiting high temperature stability and high thermal conductivity. As a ceramic material it has been widely used for thermal management, heat shielding, lubrication, and as a filler material for structural composites. Recent scientific advances in isolating atomically thin monolayers from layered van der Waals crystals to study their unique properties has propelled research interest in mono/few layered h ‐BN as a wide bandgap insulating support for nanoscale electronics, tunnel barriers, communications, neutron detectors, optics, sensing, novel separations, quantum emission from defects, among others. Realizing these futuristic applications hinges on scalable cost‐effective high‐quality h ‐BN synthesis. Here, the authors review scalable approaches of high‐quality mono/multilayer h‐ BN synthesis, discuss the challenges and opportunities for each method, and contextualize their relevance to emerging applications. Maintaining a stoichiometric balance B:N = 1 as the atoms incorporate into the growing layered crystal and maintaining stacking order between layers during multi‐layer synthesis emerge as some of the main challenges for h ‐BN synthesis and the development of processes to address these aspects can inform and guide the synthesis of other layered materials with more than one constituent element. Finally, the authors contextualize h ‐BN synthesis efforts along with quality requirements for emerging applications via a technological roadmap. Abstract : Scalable approaches of high‐quality mono/multilayer hexagonal boron nitride ( h‐ BN) synthesis are reviewed, the challenges and opportunities for each method are discussed, and their relevance to emerging applications is contextualized. Maintaining stoichiometric balance B:N = 1 in the growing crystal and enabling stacking order between layers emerge as the main challenges. Advances in these aspects will inform/guide the synthesis of other 2D materials with >1 constituent element.